Consumer in Sustainable Textiles: A Scientometric Review - Can Cui; Nazlina Shaari (Textile & Leather Review, 2023)
In the realm of textiles, numerous brands are endeavouring to embrace sustainable development and prioritize consumer orientation. Nevertheless, during the actual sales process, sustainability is frequently communicated to consumers through the medium of sustainable fabrics, often failing to elicit profound resonance among them. This study uses scientometry to conduct a comprehensive and quantitative analysis of the current status of the textile industry based on consumers, aiming to explore the current situation and development direction between consumers and the sustainable behaviour of the textile industry. From 2014 to 2023, the Scopus database included 1010 articles related to the clothing field, based on user-oriented research. The analysis results of this study are as follows: 50 research keywords appear in the knowledge base; 8 current research areas; 10 research hotspots; 10 important knowledge references in this field; Practitioners have a better understanding of the current status and trends of sustainable development in the clothing field under user guidance. The research results provide suggestions for the sustainable development of the textile industry, promote effective communication between the textile industry and consumers on a sustainable level, and help improve the consumer stickiness and sustainable development of the textile industry.